Web Dynpro ABAP for Practitioners - Gellert, Ulrich. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
Web Dynpro ABAP, a NetWeaver web application user interface tool of SAP enables web programming connected to SAP Systems. The main focus of the authors was to create a book based on practical experience. Each chapter includes examples which lead through the content step-by-step and enable the reader to gradually emerge in the topic of the Web Dynpro ABAP process. The authors explain in particular how to design a Web Dynpro component, the data binding and inteface methods, and the view controller methods. They also describe the other SAP NetWeaver Elements (ABAP Dictionary, Authorization) and the integration of the Web Dynpro Application into the SAP NetWeaver Portal.